Media ethics : issues and cases - Patterson, Philip; Wilkins, Lee (McGraw-Hill Higher Education, 2008)
Combining hypothetical cases with an introduction to ethical theory, this book helps students prepare for the ethical situations they encounter in the media professions. This book reflects changes in the world post 9/11, including the war in Iraq, the Enron and WorldCom scandals, and a look at media and democracy in light of FCC-approved media.